Penggunaan Ekstrak Daun Sirsak (Annona muricata L) Terhadap Kemampuan Pro-Apoptosis Sel Kanker Pada Tubuh Manusia : Studi Cellular Pathway Melalui Tinjauan Pustaka - Bakar, Abu; SSN, R. Moch Satrio (Maliki Interdisciplinary Journal, 2025)
Introduction: Cancer remains a major global health challenge, with many treatments still proving ineffective. Soursop leaf extract (Annona muricata L.), used in traditional medicine, has shown promise as an anti-cancer agent. Its effectiveness is largely due to acetogenins, compounds that induce apoptosis in cancer cells. Apoptosis is essential for regulating cell growth and preventing uncontrolled proliferation. Purpose:This study evaluates the potential of soursop leaf extract to induce apoptosis in cancer cells through cytokine signaling pathways. Methods: A literature review was conducted using databases like PubMed and Semantic Scholar with keywords related to cancer, apoptosis, and Annona muricata L. Articles were selected based on their relevance to cancer cell research and the use of soursop leaf extract. Results: The review found that soursop leaf extract inhibits anti-apoptotic proteins Bcl-2 and Bcl-x, while activating pro-apoptotic proteins such as p53. Additionally, it triggers the intrinsic apoptosis pathway by stimulating cytochrome c release from mitochondria, thereby hindering cancer cell growth. Conclusion: Soursop leaf extract shows significant potential as a pro-apoptotic agent for cancer therapy. It provides a basis for developing safer and more effective natural cancer treatments. Further research and clinical trials are needed to confirm its efficacy and safety, paving the way for its integration into future cancer treatment strategies.